Influenza vaccine is able to prevent neuroinflammation triggered by H7N7 IAV infection - Luisa Demuth; Melanie Ohm; Kristin Michaelsen-Preusse; Kai Schulze; Peggy Riese; Carlos A. Guzmán; Martin Korte; Martin Korte; Shirin Hosseini; Shirin Hosseini (Frontiers Media S.A., 2023)
Influenza A virus (IAV) subtypes are a major cause of illness and mortality worldwide and pose a threat to human health. Although IAV infection is considered a self-limiting respiratory syndrome, an expanded spectrum of cerebral manifestations has been reported following IAV infection. Neurotropic IAVs, such as the H7N7 subtype, are capable of invading the central nervous system (CNS) and replicating in brain cells, resulting in microglia-induced neuroinflammation. Microglial cells, the brain's resident immune cells, are instrumental in the inflammatory response to viral infection. While activation of microglia is important to initially contain the virus, excessive activation of these cells leads to neuronal damage. Previous studies have shown that acute and even long-term IAV-induced neuroinflammation leads to CNS damage. Therefore, the search for possible preventive or therapeutic strategies is of great importance. In this study, we investigated the potential effect of vaccination against acute neuroinflammation induced by H7N7 infection and subsequent neuronal damage in the hippocampus, a particularly vulnerable brain region, comparing young and aged mice. Immunosenescence is one of the striking pathophysiological changes during mammalian aging that leads to "inflammaging" and critically limits the protection by vaccines in the elderly. The results suggest that formalin-inactivated H7N7 vaccine has a preventive effect against the inflammatory responses in the periphery and also in the CNS after H7N7 infection. Cytokine and chemokine levels, increased microglial density, and cell volume after H7N7 infection were all attenuated by vaccination. Further structural analysis of microglial cells also revealed a change in branching complexity after H7N7 infection, most likely reflecting the neuroprotective effect of the vaccination. In addition, synapse loss was prevented in vaccinated mice. Remarkably, engulfment of post-synaptic compartments by microglia can be proposed as the underlying mechanism for spine loss triggered by H7N7 infection, which was partially modulated by vaccination. Although young mice showed better protection against neuroinflammation and the resulting deleterious neuronal effects upon vaccination, a beneficial role of the vaccine was also observed in the brains of older mice. Therefore, vaccination can be proposed as an important strategy to prevent neurological sequelae of H7N7 infection.